Remineralization potential of dentifrice containing nanohydroxyapatite on artificial carious lesions of enamel: A comparative in vitro study - Nithin Manchery; Joseph John; Nagappan Nagappan; Gireesh Kumar Subbiah; Parvathy Premnath (Wolters Kluwer Medknow Publications, 2019)
Background: A carious lesion is the accumulation of numerous episodes of demineralization and remineralization, rather than a unidirectional demineralization process. Tooth destruction can be arrested or reversed by the frequent delivery of fluoride or calcium/phosphorous ions to the tooth surface. Nanohydroxyapatite particle-containing dentifrices are the newer generation of products which claim to remineralize enamel lesions effectively. The aim of this study was to evaluate and compare the remineralization ability of dentifrices containing nanohydroxyapatite, NovaMin, and amine fluoride on artificial enamel caries. Materials and Methods: In this in vitro study, extracted sound premolars were placed in a demineralizing solution to produce deep artificial carious lesions. The teeth were then sectioned longitudinally and divided into three groups (n = 16 in each group): Group A (nanohydroxyapatite), Group B (NovaMin), and Group C (fluoride). The sections were then subjected to pH cycling for 7 days. Polarized light microscopy was utilized to record the depth of the lesions before and after treatment with the selected dentifrices. Changes in the mean lesion depth were statistically analyzed by one-way ANOVA and t-test. The level of significance was assessed at P < 0.05. Results: The lesion depth decreased significantly by 10.56% in Group A, 6.73% in Group B, and 9.58% in Group C (paired t-test, P < 0.001). When comparisons were made across the groups, no statistical significance was found between the Groups A, B, and C (ANOVA test, P > 0.05). Conclusion: All three dentifrices were found to be effective in remineralizing artificial carious lesions. Nanohydroxyapatite dentifrice produced significantly better results compared to fluoride- and NovaMin-containing dentifrices, instigating for its use in the management of early carious lesions.